Frequency and prognostic impact of acute kidney injury in patients with acute pulmonary embolism. Data from the RIETE registry - Martin Murgier; Laurent Bertoletti; Michael Darmon; Fabrice Zeni; Reina Valle; Jorge Del Toro; Pilar Llamas; Lucia Mazzolai; Aurora Villalobos; Monreal, Manuel and the RIETE Investigators; Bosevski, Marijan; Zdraveska, Marija; et al. (My University, 2019)
Rationale: Acute kidney injury (AKI) is associated with a poor outcome. Although pulmonary embolism (PE) may promote AKI through renal congestion and/or hemodynamic instability, its frequency and influence on outcome in patients with acute PE have been poorly studied. Methods: The frequency of AKI (defined according to the "Kidney Disease: Improving Global Outcomes" definition) at baseline and its influence on the 30-day mortality was evaluated in patients with acute PE from the RIETE (Registro Informatizado Enfermedad TromboEmbolica) registry. We used multivariate analysis to assess whether the presence of AKI influenced the risk for 30-day death. Results: The study included 21,131 patients, of whom 6222 (29.5%) had AKI at baseline: 4385 patients (21%) in stage 1, 1385 (6.5%) in stage 2 and 452 (2%) in stage 3. The proportion of patients with high-risk PE in those with no AKI, AKI stage 1, AKI stage 2 or AKI stage 3 was: 2.8%, 5.3%, 8.8% and 12%, respectively (p < 0.001). After 30 days, 1236 patients (5.9%) died. Overall mortality was 4% in patients with no AKI, 8.4% in AKI stage 1, 14% in AKI stage 2 and 17% in AKI stage 3 (all p < 0.001). AKI was independently associated with an increased risk of all-cause death at 30 days (odds ratio = 1.25; 95%CI: 1.02-1.54). Conclusions: One in every 3-4 patients with acute PE had AKI at baseline. The presence of AKI independently predicted 30-day mortality. This study suggests that AKI may deserve to be evaluated as a prognostic factor in patients with acute PE.
Keywords: Acute kidney injury; Biomarkers; Bleeding; Mortality; Pulmonary embolism; Risk